试析抗战统 ：战线“文协”下的内部矛盾 ：以“延安派”与“胡风派”为中心 = Analyzing the internal conflict within “all-China anti-Japanese writers federation” : using “Yan-an group” and “Hu Feng group” as examples - 覃文惠 Shum, Wen Hui (2014)
1937 年“七七卢沟桥事变”爆发，日军开始全面侵入中国，全国人民纷纷高举救国的旗帜投入抗日斗争。 原本散乱的文艺界也因为抗战的需要成立了“中华全国文艺界抗敌协会”（简称“文协”），以实现文艺界团结起来，为中国文艺史上创下了创举。本文旨在探讨“文协”在抗战的历史背景下如何让分歧严重的文艺界团结起来，以及在“文协”的领导下左派内部却又有矛盾的出现。在抗战正式爆发和“文协”成立前，文艺界因为各流派主张的文艺思想理论不同而导致文艺界里分歧的状态，其中“两个口号”论争是抗战前最激烈的一场论争。随着抗战的爆发，文艺界领悟到团结抗日的需要，从而暂时放下各自的主见，成立“文协”以一致抗日。然而，这一时期的文艺界虽然是在举着抗日的旗帜，但是在文艺思想理论上却又出现了严重的分歧，再加上抗战时的政治因素也造成文艺界陷入更复杂的局面。本文通过分析当时所发表的文章来探讨“文协”如何在抗战的需要下成立，并研究当时的文艺界状态。本文认为，“文协”虽然是举着抗日团结的旗帜，但是文艺界内部却依然有分歧的现象，所以实际上只是在营造一个团结的假象。The “LuGou Bridge” Incident that occurred on 7 July 1937 marked the beginning of the War of Resistance against Japan in China, resulting in the Chinese joining forces and uniting to fight against the enemies. Due to the needs to unite during wartime, the circle of literary and art which was divided initially came together to establish an association named “All-China Anti-Japanese Writers Federation” (also known as “All-China Writers Federation”). The establishment of this association brought about the unity within the literary and art circle, creating a great pioneering work in the history of literary and art. The main objective of this research is projected to analyze how the “All-China Writers Federation” aims to unite the literary and art circle during wartime and how internal conflicts among the leftist happened concurrently. Before the outbreak of the war and establishment of the “All-China Writers Federation”, the literary and art circle were in a greatly divided state as different literature groups were formed base on different theories of literary and art. Due to the differences in their theories, the debate on the “Two Slogans” was one of the most intense debates just before the war. However, due to the outbreak of the war, the literary and art circle realized the need to unite and fight against the enemies. Eventually, the different literature groups put aside their differences, established “All-China Writers Federation” and worked together through literary and art activities. Although the literature and arts circle aim to unite and fight against the enemies, the division of their literature and arts theories still existed, and coupled with the political factors during wartime, the literature and arts circle became much more complex. Hence, the thesis will study the articles released during the wartime so as to analyze how the “All-China Writers Federation” was established as well as the situation of the literary and arts circle under the association’s lead. The conclusion shows that even though the “All-China Writers Federation” is an association that aims to unite and fight against the enemies, the literary and arts circle was still in a divided state, causing the united front created by the association to be a facade.